(untitled) (Research, Society and Development, 2020)
The aim of the study was to identify stress levels and social profile in postgraduate healthcare students from the Regional University of Cariri - URCA at its Campus in Crato, Ceara. This is a quantitative, descriptive, and cross-sectional study done with 44 of the postgraduate students, being 14 of them from the Academic Master’s Degree in Nursery, and 30 of them from the Multi-professional Residency in Collective Health. The data gathering was made through a sociodemographic, academic, and lifestyle variables questionnaire. The Job Stress Scale was used to calculate psycho-social stress in the formulation of quadrants from Karasek’s Demand-control model (1979). It defines the categories: low strain jobs (low demand and high control), passive jobs (low income and control), active jobs (high demand and control) and high strain jobs (high demand and low control). The population in this study was predominantly composed of women (77,27%) ages 26 to 30 (43,18%), catholic (72,73%), single students (70,45%) with incomes superior to four minimum wages (45,45%), no children (90,91%), scholarship holders (84,09%) who work 60 hours a week and are exclusively dedicated to their occupations (68,18%). The high demand was present in 87,9% of the postgraduate students’ routines. The high strain was present in 81,4% of them, making evident, yet, a high social support. The category of the quadrants that included the bigger amount of people in it was active jobs (77,72%). According to the results, we could see that active jobs was predominant, with high psychological demands and control, besides high social support.